Potencial da nanoemulsão do óleo essencial de patchouli Pogostemon cablin Benth. (Lamiaceae) para controle de Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Scolari, Andressa Soares (2025)
The fall armyworm Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) is one of the main migratory pests that affects several crops, including corn Zea mays L. (Poaceae). Chemical control and the use of genetically modified plants are the main tactics used to control S. frugiperda. However, the intensive use of synthetic insecticides and the lack of adoption of refuge areas in genetically modified crops have caused the selection of resistant insect populations. In the search for new molecules to control S. frugiperda, botanical insecticides can be used. Therefore, one of the limiting factors for commercialization is the development of new formulations, especially those using nanotechnology. Therefore, nanoformulations appear to be promising to overcome this problem. Therefore, the objective of this study was to evaluate the toxicity of the nanoemulsion of the essential oil (EO) of Pogostemon cablin Benth. (Lamiaceae) (nano-EO) for S. frugiperda caterpillars in a greenhouse. The nano-EO of P. cablin was obtained and characterized in previous studies. The negative controls used were water, 1% Tween 80 aqueous solution and blank nanoemulsion (nanoemulsion components without EO). The other treatments were: P. cablin EO (5 mg of EO/mL) and nano-EO (5 mg of nanoformulated EO/mL), which were previously solubilized in 1% Tween 80 aqueous solution. For all treatments, the spray was applied using an airbrush (5 mL/plant). The design was completely randomized with 20 replicates per treatment. Each experimental plot consisted of one plant, in which 3 caterpillars were inoculated and kept individually by clip-type cages. The assay was evaluated every 24 h and interrupted at 168 h. Nano-EO was more toxic to caterpillars than EO, the probability of survival of insects was 40% and the median lethal time (LT50) was 96 h. Whereas for EO, the probability of survival was 72.4% and the LT50 ≥ 120H. It can be concluded that nano-EO has properties that make it more toxic to S. frugiperda than in its unformulated form.